RETRACTED ARTICLE: Research on the efficacy of Celastrus Orbiculatus in suppressing TGF-β1-induced epithelial-mesenchymal transition by inhibiting HSP27 and TNF-α-induced NF-κB/Snail signaling pathway in human gastric adenocarcinoma - Yaodong Zhu; Yanqing Liu; Yayun Qian; Xiaojun Dai; Ling Yang; Jue Chen; Shiyu Guo; Tadashi Hisamitsu (BMC Complementary and Alternative Medicine)
Abstract Background Celastrus orbiculatus has been used as a folk medicine in China for the treatment of many diseases. In the laboratory, the ethyl acetate extract of Celastrus orbiculatus (COE) displays a wide range of anticancer functions. However, the inhibition of the metastasis mechanism of COE in gastric cancer cells has not been investigated so far. Methods The present study was undertaken to determine if the anti-metastasis effect of COE was involved in inhibiting of epithelial–mesenchymal transition (EMT) of human gastric adenocarcinoma SGC-7901 cells. In vitro, a well-established experimental EMT model involving transforming growth factor β1 (TGF-β1) was applied. Viability, invasion and migration, protein and mRNA expression of tumor cells were analyzed by MTT assay, transwell assay, western blot and real-time PCR, respectively. The molecular targets of COE in SGC-7901 cells were investigated by two-dimensional gel electrophoresis (2-DE) and MALDI-TOF-TOF mass spectrometer. Overexpression of heat shock protein 27 (HSP27) was performed by transfected with the recombinant retroviral expression plasmid. In vivo, the anti-metastasis mechanisms of COE in the peritoneal gastric cancer xenograft model was explored and the effect was tested. Results The non-cytostatic concentrations of COE effectively inhibited TGF-β1 induced EMT process in SGC-7901 cells, which is characterized by prevented morphological changes, increased E-cadherin expression and decreased Vimentin, N-cadherin expression. Moreover, COE inhibited invasion and migration induced by TGF-β1. Using a comparative proteomics approach, four proteins were identified as differently expressed, with HSP27 protein being one of the most significantly down-regulated proteins induced by COE. Moreover, the activation of nuclear factor κB (NF-κB)/Snail signaling pathway induced by tumor necrosis factor-α (TNF-α) was also attenuated under the pretreatment of COE. Interestingly, overexpression of HSP27 significantly decreases the inhibitory effect of COE on EMT and the NF-κB/Snail pathway. Furthermore, COE significantly reduced the number of peritoneal metastatic nodules in the peritoneal gastric cancer xenograft model. Conclusions Taken together, these results suggest that COE inhibits the EMT by suppressing the expression of HSP27, correlating with inhibition of NF-κB/Snail signal pathways in SGC-7901 cells. Based on these results, COE may be considered a novel anti-cancer agent for the treatment of metastasis in gastric cancer.